2022
DOI: 10.1039/d1cy01810h
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the interactions of reductants and reaction path over Cu-ZSM-5 for model coal-gas-SCRviaa transient reaction study

Abstract: with coal gas can be a solution for NOx emission control in iron and steel industry, nevertheless the coal-gas- is not clearly understood and hard to study due to the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Based on a previous study, 17 we screened more Cu modified zeolite catalysts with different topological structures ( e.g. ZSM-5, SSZ-13, and SAPO-34) for the coal-gas-SCR process (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a previous study, 17 we screened more Cu modified zeolite catalysts with different topological structures ( e.g. ZSM-5, SSZ-13, and SAPO-34) for the coal-gas-SCR process (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…If coal gas could be used instead of ammonia as the reducing agent, it will have great benefit on the investment cost and operation cost of deNO x for the iron and steel industry due to easier access and the much lower price of coal gas. Based on the enormous practical implication prospect in the iron and steel industry, the selective catalytic reduction of NO by coal-gas (coal-gas-SCR) was first proposed and studied over Cu-zeolites in our previous work, 17 in which interactions between reductants (CO, H 2 , and CH 4 ) and mechanisms were clarified. However, for this complicated reaction system, the structure-function relationship for Cu-zeolite catalysts is still undone.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the traditional commercial V 2 O 5 -WO 3 /TiO 2 catalysts, many studies have focused on the development of low-temperature SCR catalysts, including metal oxide-based catalysts, like Fe, 13,14 Mn, 15,16 Ce, 17 Cr, 18 W, 19 Cu, 20,21 and zeolite-based catalysts, like CuSn/ZSM-5 22 and Cu-ZSM-5. 23 Among various catalysts, manganese-based catalysts have been widely studied and applied due to their low cost and outstanding low-temperature denitrication performance, whereby their abundant Lewis acid sites, variable valence states of Mn, and strong redox ability contribute to their excellent catalytic activity at low temperature, especially under 200 °C. 10,[24][25][26][27] For instance, Yang et al 28 found that a-MnO 2 exhibited the most superior SCR performance for NO x conversion compared with other crystal phases of b, g, and d-MnO 2 at a lower temperature of 50-120 °C.…”
Section: Introductionmentioning
confidence: 99%